(untitled) (Bangladesh Journal of Bioethics, 2012)
Youths of Bangladesh (18-35) constitute one-third of the total population. In this article, young people imply both adolescents and youth. There are 28 million adolescent populations in Bangladesh. Approximately there are sixty million young people in Bangladesh The vast majority of them are illiterate, and handicapped with severe poverty. Because of lack of family control, proper education, poverty, unemployment and peer pressure a significant portion of them are deviated from the norm of the society. In this paper four issues of moral deviation- eve teasing, drug and substance abuse, juvenile delinquency and access to pornography will be discussed. DOI: http://dx.doi.org/10.3329/bioethics.v1i3.9636 Bangladesh Journal of Bioethics 2010; 1(3): 58-62